Stemness and chemoresistance are imparted to the OC cells through TGFβ1 driven EMT. Issue 7 (14th March 2018) - Mitra, Tulika; Prasad, Parash; Mukherjee, Pritha; Chaudhuri, Susri Ray; Chatterji, Urmi; Roy, Sib S.
Abstract: Ovarian cancer (OC) is the fourth most common gynecological malignancy due to its highly aggressive, recurrent, and drug‐resistant nature. The last two features are rendered by the presence of cancer stem cells (CSCs). Factors like TGFβ1 and their downstream signaling pathways are upregulated in most cancers and are known to induce EMT and stemness, but the exact mechanisms underlying the process remain unelucidated. In our study, TGFβ1 induced enhanced stem‐like properties like high expression of the pluripotent markers SOX2, OCT4a, and NANOG, along with CD44, and CD117 in the OC cells. In addition, increased activity of the aldehyde dehydrogenase enzyme, formation of compact spheroids, and a quiescent phenotype were observed. In deciphering the mechanism behind it, our data propose ZEB1 transcription factor to play a substantial role in inducing the EMT‐mediated stemness and chemoresistance. Further, in our study, we elucidated the significant contribution of both Smad and non‐Smad pathways like ERK, JNK, and P38 MAPK pathways in the induction of stem‐like characteristics. The novelty of the study also resides with the fact in the expression of different lineage‐specific markers, like CD31, CD45, and CD117 along with CD44 in the TGFβ1‐induced epithelial ovarian cancer spheroids. This suggests a tendency of the spheroidal cells towards differentiating into heterogenic populations, which is a distinctive feature of a stem cell. Taken together, the present study provides an insight to the molecular cues involved in the acquisition of stemness and chemoresistance along with tumor heterogeneity in TGFβ1‐induced OC cells. Abstract : The study provides evidence of acquisition of stemness and chemoresistance through TGFβ1‐driven EMT. ZEB1 plays a substantial role in the process, while the role of Smad2 is diluted due to the activation of non‐Smad pathways. Drug resistance acquired by TGFβ1‐mediated upregulation of ABCG2 transporter can be reversed by the use of the inhibitor Verapamil hydrochloride.